Accelerometry Correlates in Body Composition, Physical Fitness, and Disease Symptom Burden: A Pilot Study in End-Stage Renal Disease - Sember, Vedrana; Bogataj, Špela; Ribeiro, Jose Carlos; Paravlić, Armin; Pajek, Maja; Pajek, Jernej (Frontiers in Physiology, 2021)
There is strong evidence that hemodyalysis (HD) patients with a sedentary lifestyle have a higher risk of death compared to peers who engage in regular physical activity. Therefore, monitoring physical activity is of utmost importance. However, there is a lack of data on objectively measured physical activity behaviors in HD patients. Therefore, the current study aimed to objectively measure physical activity in HD patients throughout the week, with particular attention to dialysis and non-dialysis days. We also examined how objectively measured physical activity correlated with physical fitness, body composition, and disease burden. Daily physical activity, body composition, serum parameters, comorbidity index, sit-to-stand, and hand-grip strength tests were measured in 14 HD patients. Daily physical activity was measured using the Actigraph GT9X accelerometer. The Dialysis Symptom Index questionnaire was also used. We found significant differences in anthropometric variables (weight, body mass index, overhydration, lean tissue index, fat tissue index, all p<0.05) and phase angle (p<0.01) between HD patients reaching and patients not reaching physical activity guidelines for patients with chronic diseases. HD patients showed to be less active during dialysis days compared to non-dialysis days in sedentary time (-11.7%; p = 0.001), light (-47.3%; p = 0.003), moderate (-51.5%; p = 0.001), moderate to vigorous (-49.3%; p = 0.001) and vigorous (-34.3%; p = 0.067) physical activity. No significant correlations were found between serum parameters, symptom burden and comorbidity burden, but a very large and positive correlation was found between phase angle and total MVPA (p<0.01). Our findings support the need to implement physical activity on dialysis days in HD units to mitigate the effects of sedentary behavior. Prospective, long-term studies evaluating the use of accelerometers in HD patients and their effects on physical activity are needed.